A Note on Full-Rank Factorization of Matrix - Thapa, Gyan Bahadur; López-Bonilla, J.; López-Vázquez, R. (Journal of the Institute of Engineering, 2019)
We exhibit that the Singular Value Decomposition of a matrix Anxm implies a natural full-rank factorization of the matrix.